2013
DOI: 10.1590/s1677-5538.ibju.2013.06.10
|View full text |Cite
|
Sign up to set email alerts
|

Uroflowmetry in a Large Population of Brazilian Men Submitted to a health check up program and its correlation with ipss and prostate size

Abstract: Purpose: The aim of this study was to assess the uroflowmetry data in a large population of asymptomatic Brazilian men submitted to a health check up program and their correlation to IPSS and prostate size. Materials and Methods: Asymptomatic men underwent a health check-up program between January and December 2012. The inclusion criteria were men between 40 and 70 years, IPSS ≤ 7, without bladder, prostate, urethral surgery, neurological diseases, urinary tract infection, PSA < 4.0 ng/dL and urinary volume hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…In our study we found negative relationship of Qmax with IPSS (Table 3) therefore substantial the size of gland lower was the Qmax and greater the IPSS lower was peak flow rate. Our results were in consensus with Zamboan et al they also observed negative relationship between Qmax with prostate volume and IPSS 15 Singla et al also found negative correlation of Qmax with prostate volume as prostate enlarges Qmax is increasing rather instead of decreasing values and going towards obstruction however Qmax showed no correlation with prostate volume in our study. According to recent study published in 2022 they could not find any correlation between prostate volume and Qmax 16 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study we found negative relationship of Qmax with IPSS (Table 3) therefore substantial the size of gland lower was the Qmax and greater the IPSS lower was peak flow rate. Our results were in consensus with Zamboan et al they also observed negative relationship between Qmax with prostate volume and IPSS 15 Singla et al also found negative correlation of Qmax with prostate volume as prostate enlarges Qmax is increasing rather instead of decreasing values and going towards obstruction however Qmax showed no correlation with prostate volume in our study. According to recent study published in 2022 they could not find any correlation between prostate volume and Qmax 16 .…”
Section: Discussionsupporting
confidence: 92%
“…The total score ranges from 0 to 35 (asymptomatic to symptomatic). The Symptom index is categorized as mild ( 7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and severe ( 20)". Each question is further divided into 5 question 0.…”
mentioning
confidence: 99%
“…As expected, these results differ from normal values because of the patients included. An abnormal uroflowmetry suggests abnormal micturition and the objective is early detection of bladder outlet obstruction and offer prompt treatment to avoid bladder dysfunction or complications as acute urine retention or kidney failure [6]. Outcomes in this study were: 26.3% non-obstructive patients and 73.7% obstructive patients.…”
Section: Discussionmentioning
confidence: 97%
“…Uroflowmetry must be used with caution and always with other diagnostic tools like International Prostatic Symptoms Score (IPSS) and transabdominal prostatic ultrasound with post-void urine volume [6]. There is great variability in uroflowmetry parameters, even in healthy patients, because of that it is suggested to use high normal values that diminish specificity but augment sensibility of patients with outlet bladder obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Ainda não há um parâmetro, na prática clínica diária, confiável e especifico para definir a severidade da obstrução infravesical causada pela HBP, e indicar, se ela já está instalada, porém, assintomática. Ela pode ser objetivamente documentada, mas não quantificado o grau e a severidade da obstrução, uma vez que a obstrução sem sintomas pode ocorrer (34,35) .…”
Section: O Desafio é Iniciar O Tratamento Antes Que As Alterações Ana...unclassified